The woman's way - Garvice, Charles, 1850-1920 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Woman's Way" by Charles Garvice is a novel written in the early 20th century. The story follows Celia Grant, a young woman who has recently found herself in a challenging situation after the death of her father, leaving her alone and struggling to make ends meet. The narrative explores themes of social class, self-sufficiency, and the feminine experience of hardship." "At the start of the novel, we are introduced to Celia as she climbs the stairs to her modest room in Brown's Buildings, a run-down lodging reminiscent of a prison. Through a detailed exposition, we gain insight into her meager income and frugal lifestyle. Celia's loneliness is palpable, yet she is described as a resilient character who seeks companionship in her interactions with Mr. Clendon, an elderly neighbor, and her musings about the young man living across the hall whose silence hints at deeper troubles. The opening establishes Celia$1 (Bs struggle and the mundane challenges of her life, foreshadowing emotional and dramatic developments that arise when she encounters the young man in distress, holding a revolver, urging her to take action in a moment of crisis." (This is an automatically generated summary.)s
Release date is 2006-09-30
E-text prepared by David Clarke, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Inheritance and succession -- Fiction; Young women -- Fiction; Love stories; England -- Social life and customs -- Fiction